2013
DOI: 10.1111/hepr.12146
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat predominance is associated with non‐alcoholic fatty liver disease in Japanese women with metabolic syndrome

Abstract: Women with V-type MS are more likely to have fatty liver, IGT and liver dysfunction than those with S-type MS. V-type MS is one of the significant predictors for NAFLD in Japanese women with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
2
12
0
3
Order By: Relevance
“…Also in Ordinal logistic regression, BMI was predictor for USG. As well as some explained articles, BMI is predictor of NAFLD severity or significantly higher in the patients with fatty liver (Tables 2 and 3) (26, 40, 41). AST had a prediction role in the severity of disease and U.S grade.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Also in Ordinal logistic regression, BMI was predictor for USG. As well as some explained articles, BMI is predictor of NAFLD severity or significantly higher in the patients with fatty liver (Tables 2 and 3) (26, 40, 41). AST had a prediction role in the severity of disease and U.S grade.…”
Section: Discussionmentioning
confidence: 59%
“…However, it has not been a reliable finding, because AST level changed in many conditions such as systemic disorder (Tables 2 and 3) (28, 30). Nevertheless, in several papers like Purnak T, Sogabe M and Lin YC, AST was a predictor of NAFLD severity and U.S significantly (26, 27, 29). …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Gender differences in NAFLD, MS and EO have been recently reported 57 16–18 Sogabe et al 16 17 divided MS into visceral and subcutaneous types, with each having significantly different effects on EO; they also found that the visceral type was predominant among males, while the subcutaneous type was predominant among females. However, until now, there have been no studies regarding the concomitant effects of NAFLD and MS on EO with respect to gender.…”
Section: Introductionmentioning
confidence: 93%
“…Masahiro Kikuchi 1 symptoms resembling those of alcoholic liver dysfunction and the number of patients are increasing along with the increase in that of patients with metabolic syndrome 3) . NAFLD is recognized as an expression type of metabolic syndrome in the liver, so its disease concept has become widely known by the public.…”
Section: Nonalcoholic Steatohepatitis As Fatal Fatty Liver -The Next mentioning
confidence: 99%